Heterogeneity in the price response of residential electricity demand: A dynamic approach for Germany - Manuel Frondel; Gerhard Kussel; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
To provide the basis for evaluating the effectiveness of price policies, this paper contributes to the literature by estimating the heterogeneity in the response of residential electricity demand to price increases across household types. Drawing on household panel data from the German Residential Energy Consumption Survey (GRECS) that span over nine years (2006-2014), we gauge the response of residential electricity demand to price increases on the basis of the dynamic Blundell-Bond estimator to account for potential simultaneity and endogeneity problems, as well as Nickell bias. Estimating short- and long-run price elasticities of -0.44 and -0.66, respectively, our results indicate that price measures may be effective in dampening residential electricity consumption, particularly in the long run. Yet, we also find that responses to price changes are very heterogeneous across household groups, an outcome that has important implications for policy-making. Most notably, we do not find any significant price response for lowincome households. – – Um eine Basis zur Bewertung der Effektivität von Preispolitiken zu liefern, untersucht dieses Papier die Heterogenität in der Preisreagibilität des Stromverbrauchs privater Haushalte für unterschiedliche Haushaltstypen. Auf Basis der Paneldaten des German Residential Energy Consumption Survey (GRECS) für die Jahre 2006-2014 werden Preiselastizitäten auf Basis des dynamischen Blundell-Bond-Schätzers ermittelt, um wahrscheinliche Endogenitätsprobleme zu berücksichtigen und den Nickell bias zu vermeiden. Kurz- und langfristige Preiselastizitäten von -0,44 und -0,66 deuten darauf hin, dass Preispolitiken effektive Maßnahmen zur Senkung des Stromverbrauchs im Haushaltssektor sein können. Wir finden allerdings auch, dass die Preisreagibilität für verschiedene Haushaltstypen sehr heterogen ausfällt. Vor allem Haushalte mit geringem Einkommen zeigen keine Reaktion auf Strompreisänderungen.
Keywords: C23; C26; D12; Q41; 330; dynamic panel methods; instrumental variable approach